Eksistensi dan Peran Dakwah: Studi Dakwah Tuan Guru Sujarman - Rohimi, Rohimi (Institut Agama Islam Syarifuddin Lumajang, 2021)
Da'wah is a form of invitation or invitation to give views on Islam. Da'wah is also a very noble form of work, because it aims to be able to invite people to do good and be useful for the life of the world both in the hereafter. In this study, researchers will examine the existence of the indictment Tuan Guru Sujarman in Kelambi Hamlet, Pandan Indah Village. Because before the preaching of Tuan Guru Sujarman in Kelambi Hamlet, people tended not to be very keen on participating in da'wah activities, for example only following da'wah studies only on certain Islamic days. In addition, before the preaching of Tuan Guru Sujarman in Kelambi Hamlet, there was a tendency for children to only choose to enter public education. Therefore, this is one of the focus of discussion in this study, regarding the existence of Tuan Guru Sujarman's preaching in enhancing the religious behavior of early childhood through his preaching. The results and discussion in this study, that the message of Tuan Guru has an impact on increasing children's interest and also opens the way parents think about the importance of education for children in the pesantren environment. Where after the preaching of Tuan Guru Sujarman, it made the community intensify in following Islamic studies and made transformative education for children from the state to Islamic boarding schools.Keywords : Islamic Community Development, Da'wah, Tuan Guru Sajarman